Pengeluaran Pemerintah dan Pertumbuhan Ekonomi: Hipotesis Keynes Versus Teori Wagner - Surgawati, Iis (WELFARE Jurnal Ilmu Ekonomi, 2020)
The main purpose of this study was to analyze the relationship between government expenditure, especially on human resource development and economic growth, and paradoxically observed between Keynes hypotheses and Wagner theory of West Java economies. The data used are secondary unbalanced panel data from 27 districts / cities for the period of 2010 - 2017. The estimated model used on the entire data is Two Stage Least Square approach, Fixed Effect Model. The results showed that (i) government expenditure on human resource development and urban structure were significantly positive effect, region characteristic and the global financial crisis were significantly negative effect, labor and democratic development has a negative effect as well as the quality of the institution has a positive effect but not significant on economic growth, (ii) economic growth, population and total government expenditure were significantly positive effect, the financial crisis and the quality of institutions have a positive effect as well as the characteristics of the region and the development of democracy have negative effect but not significant on government expenditure on human resources development, (iii) the economy of West Java pattern tends to follow the Wagner theory.Tujuan utama penelitian ini adalah menganalisis hubungan keterkaitan antara pengeluaran pemerintah, khususnya untuk pembangunan sumber daya manusia dan pertumbuhan ekonomi serta mengamati paradoksal hipotesis Keynes dan teori Wagner pada perekonomian Jawa Barat. Data yang digunakan adalah data sekunder berupa unbalance panel data 27 kabupaten/kota periode 2010 – 2017. Model estimasi yang digunakan adalah Two Stage Least Square melalui pendekatan Fixed Effect Model. Hasil penelitian menunjukkan bahwa (i) Pengeluaran pemerintah untuk pembangunan sumber daya manusia dan struktur urban berpengaruh positif signifikan, karakteristik daerah dan krisis keuangan global berpengaruh negatif signifikan, tenaga kerja dan perkembangan demokrasi masing-masing berpengaruh negatif serta kualitas institusi berpengaruh positif tetapi tidak signifikan terhadap pertumbuhan ekonomi, (ii) Pertumbuhan ekonomi, jumlah penduduk dan pengeluaran pemerintah total berpengaruh positif signifikan, krisis keuangan dan kualitas institusi berpengaruh positif serta karakteristik daerah dan perkembangan demokrasi berpengaruh negatif tetapi tidak signifikan terhadap pengeluaran pemerintah untuk pembangunan sumber daya manusia, (iii) Pola perekonomian Jawa Barat cenderung mengikuti teori Wagner.